Pengaruh Pemberian Tugas Terhadap Hasil Belajar Siswa Kelas VIII-B Pada Mata Pelajaran Fiqih SMP Darul Hikmah Langkap Burneh Bangkalan - Sahroh, Rifatus; Damayanti, Alfina; Hasan, Mushohihul (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
Education is something that must be taken by every human being. In teaching and learning, there must be a phase where the teacher explains to the students then the students are given tasks according to the lessons given by the teacher. This is certainly a reference to how students understand about the lesson. In this study, the authors used a quantitative method, method used is simple linear regression using the assignment variable (X) and the dependent variable, namely learning outcomes (Y). The next stage, the questionnaire was analyzed with a simple linear regression which serves to prove the research hypothesis. The data that has fulfilled the validity test, reliability test and assumption test are processed to produce the following regression: Y : 0.876 X : 0.648 Testing the hypothesis using the T test shows that variable X (assignment) has a positive but significant effect on variable Y (learning outcomes). The R Square number is 0.21, so the results of the termination are 0.21% which explains that giving assignments (X) results in learning (Y). That is 021 and the rest is influenced by other variables.